Relationship between the direction of diurnal rainfall migration and the ambient wind over the Southern Sumatra Island. Issue 3 (3rd March 2017) - Yanase, A.; Yasunaga, K.; Masunaga, H.
Abstract: This study investigates the climatological relationship between diurnal rainfall migration and the ambient wind over the southern Sumatra by using observation and reanalysis of 15 years of data from the Tropical Rainfall Measuring Mission satellite precipitation radar. When winds in the lower troposphere (1000–500 hPa) are westerly, convective rainfall systems migrate eastward, while rainfall systems dominated by stratiform precipitation propagate to the west in association with mid‐upper level easterly winds. When the winds are easterly throughout the troposphere, both convective and stratiform precipitation systems propagate only to the west. Rainfall system migration appears to be generally consistent with ambient zonal wind. It is suggested that the advection by background wind is, in general, a dominant component of the propagation mechanism of diurnal rainfall. Key Points: The climatological relationship between the diurnal migration of rainfall and ambient wind is clarified The diurnal characteristics of rainfall‐system migration depend systematically on the background wind Advection by background wind is suggested to be an important component of the diurnal rainfall propagation mechanism